NILAI KEMASYARAKATAN SUKU DAYAK KENYAH DALAM CERITA RAKYAT BURUI - Kaniah, Kaniah (International Conference on Humanity Education and Society (ICHES), 2024)
The Dayak Kenyah tribe keeps a wealth of traditions. One of them is folklore. Folklore is a picture of community life that is told to posterity in order to preserve cultural values that developed in society at that time. Burui is the story of a young man who lives as an orphan. The story is interesting and holds many community values of the Dayak Kenyah Lepoq tribe, Jalan Desa Lung Anai, so it needs to be explored and conveyed the content of community values. The story of Burui has never been studied. How societal values are contained in Burui folklore and whether they still need to be maintained, is a problem in this study. Considering the Dayak Kenyah Lepoq Tribe This road is in East Kalimantan which will become the capital of the archipelago which will have a lot of impact on the order of their community life. The purpose of this study is to describe the social values that exist in Burui folklore and the sustainability of these values in society. This research method is qualitative. Data collection was carried out by interview method and supplemented by literature study. Data analysis uses descriptive methods with interpretive techniques. The results showed that Burui folklore contains six societal values.